PENGARUH UPAH, USIA, TINGKAT PENDIDIKAN, DAN MASA KERJA TERHADAP PRODUKTIVITAS KERJA KARYAWAN (STUDI PADA UD. TIBAN JAYA ROTAN MALANG) - Adhitya Octoryan (Jurnal Ilmiah Mahasiswa FEB, 2016)
This study aims to determine the effect of wages, age, education level, and working duration on the employee’s productivity at UD. Tiban Jaya Rotan Malang. This study uses a quantitive approach. The data used are primary data. The method used to collect data in this research is by distributing quetionnaries and conducting interviews. The independent variables in this study is wages (X1), age (X2), education level (X3), and working duration (X4), as well as the dependent variable, namely employee’s productivity (Y). Based on the result of this reaserch is that the regression equation is found determinant coefficient (R2) was 0,755 which means the variables x1, x2, x3, and x4 affects the employee’s productivity at UD. Tiban Jaya Rotan Malang is 75,5% and the rest is influenced by other variables. If viewed from the influence of each independent variable on the  dependent variable it can be seen that the variables x1, x2, x3, and x4 have a significant effect on employee’s productivity. The variable of working duration (x4) becomes the most dominant variable. While the value of wage variable coefficient (X1) is 0,191, age variable (X2) 0,371, education level variable (X3) 0,248.Keywords: Labor, Productivity, Wages, Age, Education Level, Employee’s productivity